THU0179 Tofacitinib, an Oral Janus Kinase Inhibitor, for the Treatment of Rheumatoid Arthritis: Safety and Efficacy in Open-label, Long-term Extension up to 6 Years. (9th June 2015) - Wollenhaupt, J.; Silverfield, J.; Lee, E.B.; Wood, S.P.; Terry, K.K.; Nakamura, H.; Kwok, K.; Anisfeld, A.; Nduaka, C.; Wang, L.
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). Objectives: To report tofacitinib safety, tolerability, and durability of response up to 72 months (mo) in long-term extension (LTE) studies. Methods: Data were from 2, open-label studies: A3921024 (NCT00413699 [ongoing; database unlocked as of April 2014 data cut-off]) and A3921041 (NCT00661661 ). Patients (pts) had RA and participated in randomised Phases (P)1/2/3 tofacitinib studies. Treatment was initiated with tofacitinib 5 or 10 mg BID as monotherapy or with background DMARDs; data for both doses ± background DMARDs were pooled. Primary endpoints: AEs and laboratory safety. Confirmed data are reported for decreased haemoglobin (HgB), neutrophil, and lymphocyte counts, and increases >50% from baseline (BL) in creatinine. Secondary endpoints: ACR responses, DAS28-4(ESR), and HAQ-DI. Safety data were included over 84 mo and efficacy up to Mo 72 (n≤29 pts, post-Mo 72). Results: 4858 pts were treated (mean [max] duration: 918 [2535] days). BL data were from index studies for 91% of pts. Total tofacitinib exposure was 12 359 pt-years (py). In total, 1747 pts (36.0%) discontinued (AEs: 882 [18.2%]; insufficient clinical response: 133 [2.7%]). Most common classes of AEs: infections and infestations (63.4%), musculoskeletal/connective tissue disorders (33.9%), and GI disorders (29.9%). Most frequently reported AEs: nasopharyngitis (16.3%), upper respiratory tract infection (14.5%), and urinary tract infection (10.3%). SAEs occurred in 23.0% of pts (incidence rate [IR] 9.9/100 py [95% confidence interval [CI]; 9.4, 10.5]) and serious infections in 7.2% (IR 2.9/100 py [95% CI; 2.6, 3.2]). Malignancies (excluding NMSC) were reported in 2.5% of pts (IR 1.0/100 py [95% CI; 0.8, 1.2]). IRs for SAEs, serious infections, and malignancies up to Mo 84 did not increase vs previously reported data (Mo 72). 1 Decreased Hgb (>2g/dL change from BL or Hgb <8 g/dL) occurred in 6.1% of pts and increased aminotransferases (>3× ULN) in 1.6% (ALT) and <1.0% (AST) of pts. Moderate to severe neutropenia (absolute neutrophil count [ANC] 0.5–1.5×10 3 /mm 3 ) was reported in 1.3% of pts. No pts had ANC <0.5×10 3 /mm 3 . Absolute lymphocyte counts <0.5×10 3 /mm 3 were reported in 1.1% of pts. Increases >50% from BL in creatinine occurred in 3.1% of pts. ACR20, ACR50 and ACR70 response rates for tofacitinib were sustained to Mo 72 (80.8%, 61.5% and 35.9%). Mean DAS28-4(ESR) was 6.29 at BL, 3.74 at LTE Mo 1 and 3.32 at Mo 72. Mean HAQ-DI score was 1.42 at BL, 0.81 at LTE Mo 1 and 0.77 at Mo 72. Conclusions: A consistent safety profile and sustained efficacy up to 72 mo was observed in pts with RA receiving tofacitinib 5 or 10 mg BID in LTE studies. References: Wollenhaupt J et al. J Rheumatol 2014; 41: 837-852 Acknowledgements: Previously presented (Wollenhaupt J et al. Arthritis Rheum 2014; 66 (11): S375 abs 849) and reproduced with permission from Arthritis and Rheumatism. All aspects of this study were funded by Pfizer Inc. Editorial support was provided by Claire Cridland of Complete Medical Communications and funded by Pfizer Inc. Disclosure of Interest: J. Wollenhaupt Consultant for: Pfizer Inc, Speakers bureau: Pfizer Inc (speaker fees), J. Silverfield Grant/research support from: Pfizer Inc, Speakers bureau: Pfizer Inc (speaker fees), E. B. Lee Consultant for: Pfizer Inc, S. P. Wood Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, K. Terry Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, H. Nakamura Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, K. Kwok Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, A. Anisfeld Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Nduaka Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc